2014
DOI: 10.1007/s10620-014-3349-2
|View full text |Cite
|
Sign up to set email alerts
|

Aspirin and Nonsteroidal Anti-Inflammatory Drug Use and the Risk of Barrett’s Esophagus

Abstract: Background The use of aspirin and nonsteroidal anti-inflammatory drugs (NSAIDs) may decrease the risk of esophageal adenocarcinoma; however, it is unknown where these agents may act in the proposed pathway from normal mucosa to Barrett’s esophagus to esophageal adenocarcinoma. Aim To evaluate the association between aspirin and NSAID use and Barrett’s esophagus in a case-control study within a large community-based population. Methods We conducted a case-control study of aspirin/NSAID use and Barrett’s eso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 35 publications
1
23
0
Order By: Relevance
“…The individual study ORs may differ somewhat from the pooled ORs due to differences in confounding structure. For example, race was a strong confounder of the association between NSAID use and risk of Barrett's esophagus in KPNC (14). Here, we limited the analyses to non-Hispanic white study participants.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The individual study ORs may differ somewhat from the pooled ORs due to differences in confounding structure. For example, race was a strong confounder of the association between NSAID use and risk of Barrett's esophagus in KPNC (14). Here, we limited the analyses to non-Hispanic white study participants.…”
Section: Discussionmentioning
confidence: 99%
“…The six studies were as follows: the Houston Barrett's Esophagus study (based at the Michael E. DeBakey VA Medical Center at Houston, TX; hereafter “Houston”) (17); the Factors Influencing the Barrett's/Adenocarcinoma Relationship study (based in Ireland; “FINBAR”) (13); the Epidemiology and Incidence of Barrett's Esophagus study (based in the Kaiser Permanente Northern California population; “KPNC”) (14); The Newly Diagnosed Barrett's Esophagus Study (based at the University of Michigan and Ann Arbor Veterans Affairs Medical Center at Ann Arbor, MI; “NDB”) (18); the Study of Digestive Health (based in Brisbane, Australia; “SDH”) (16); and the Study of Reflux Disease (based in western Washington State; “SRD”) (19). We additionally restricted our analyses to non-Hispanic white study participants due to low numbers of cases from non-white ethnic groups (total n=95; range n=17 in NDB to n=43 in KPNC).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Our results are consistent with two prior hospital-and population-based retrospective case-control studies which also observed an inverse association between regular aspirin use and BE, especially for higher doses, but not between non-aspirin NSAIDs and BE. 31,32 In contrast to these results, a recent pooled analysis of data from six case-control studies in the Barrett's and Esophageal Adenocarcinoma Consortium (BEACON), found no association between regular aspirin use and BE when compared to either population or GERD controls. Similar null findings were reported for non-aspirin NSAIDs and any NSAIDs.…”
Section: Discussionmentioning
confidence: 95%
“…30 Human data regarding the association of aspirin and BE development are scant and conflicting, especially for women. Some observational studies, 17,31,32 but not all, [33][34][35][36] suggest that aspirin, but not NSAIDs, may reduce the onset of BE. Notably, a recent pooled analysis of six studies, which included 1,474 BE patients and 4,274 controls, saw no significant association between aspirin/NSAIDs and BE.…”
Section: Introductionmentioning
confidence: 99%